PENGEMBANGAN SISTEM INFORMASI AKUNTANSI MASJID (SIMAS) PADA MASJID ASH-SHOBIRIN RUNGKUT SURABAYA - Salman, Kautsar Riza; Ilham, Romi; Djunaedi, Arif Zeinfiki; Suparno, Suparno; Sa’diyah, Halimatus (Jurnal Terapan Abdimas, 2023)
Abstract. The purpose of community service is to design mosque books and accounts based on the Interpretation of Financial Accounting Standards (ISAK) 35. Community service activities focus on developing a mosque accounting information system that is designed regarding applicable accounting standards and is relevant to mosque entities. Mosque entities are classified as non-profit-oriented entities, so the accounting information system developed refers to accounting standards governing accounting for non-profit-oriented entities. namely SAK ETAP and ISAK 35. The implementation method in community service activities is currently carried out through discussion forums, training, and mentoring. Discussion forums were held with mosque administrators in the context of compiling a chart of accounts and initial trial balance. Training and mentoring are carried out concerning the input of daily transactions to prepare financial statements. The results of community service activities are software called the mosque accounting information system (SIMAS) and mosque financial statements.Abstrak. Tujuan pengabdian masyarakat adalah merancang pembukuan dan pembukuan masjid berdasarkan Interpretasi Standar Akuntansi Keuangan (ISAK) 35. Kegiatan pengabdian masyarakat fokus pada pengembangan sistem informasi akuntansi masjid yang dirancang sesuai dengan standar akuntansi yang berlaku dan relevan dengan entitas masjid. Entitas masjid tergolong entitas non profit oriented, sehingga sistem informasi akuntansi yang dikembangkan mengacu pada standar akuntansi yang mengatur akuntansi untuk entitas non profit oriented. yaitu SAK ETAP dan ISAK 35. Metode pelaksanaan dalam kegiatan pengabdian kepada masyarakat saat ini dilakukan melalui forum diskusi, pelatihan, dan pendampingan. Forum diskusi dengan pengurus masjid dilakukan dalam rangka penyusunan chart of account dan neraca saldo awal. Pelatihan dan pendampingan dilakukan mengenai input transaksi harian untuk menyusun laporan keuangan. Hasil kegiatan pengabdian kepada masyarakat berupa perangkat lunak yang disebut sistem informasi akuntansi masjid (SIMAS) dan laporan keuangan masjid.